Injury characteristics in professional modern dancers: A 15-year analysis of work-related injury rates and patterns. Issue 7 (3rd April 2022) - McBride, Caroline; Bronner, Shaw
ABSTRACT: We investigated work-related-musculoskeletal-injuries (WMSI) over 15-years in professional modern dancers to determine injury rate and pattern differences due to sex and professional-experience. Injuries were coded to allow analyses by tissue-type, body-region, severity, setting, mechanism, action-causation, and repertory-style. Injury prevalence (IP) was defined as average risk of injury/dancer. Injury incidence rate (IIR) was calculated per 1000-hrs exposure/block. Negative binomial logistic regression analyses were conducted with exposure-hrs to determine IIR, p < 0.05. Multinomial logistic regressions determined differences in tissue-type, body-region, action-causation and repertory-style; Poisson loglinear regressions determined differences in severity and mechanism, p < 0.05. Females were 15-times more likely to sustain bone-injuries, p = 0.016; males 8- and 15-times more likely to sustain muscle/tendon-injuries or lacerations/contusions, p ≤ 0.016. Females were more likely to sustain severe injury resulting in more lost-workdays and missed-performances, p < 0.001. In both sexes, more time-loss-injuries (TL-inj) occurred in performance, were traumatic in nature, with an action-causation of jumping/stomping/relevé. Dancers of moderate professional-experience were 1.3-times more likely to sustain TL-inj, p = 0.026;. Identifying context-specific activities and repertory–style relationships to injury can provide insight into casting and rehearsal scheduling. Comprehending sex-specific musculoskeletal health needs allows improved dancer health management and injury prevention planning.